The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fnins.2016.00619
|View full text |Cite
|
Sign up to set email alerts
|

Interpretability of Multivariate Brain Maps in Linear Brain Decoding: Definition, and Heuristic Quantification in Multivariate Analysis of MEG Time-Locked Effects

Abstract: Brain decoding is a popular multivariate approach for hypothesis testing in neuroimaging. Linear classifiers are widely employed in the brain decoding paradigm to discriminate among experimental conditions. Then, the derived linear weights are visualized in the form of multivariate brain maps to further study spatio-temporal patterns of underlying neural activities. It is well known that the brain maps derived from weights of linear classifiers are hard to interpret because of high correlations between predict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 93 publications
(148 reference statements)
0
12
0
1
Order By: Relevance
“…Note that contributions of individual regions were very small, however, suggesting that predictions were based on the overall pattern rather than on a small combination of regions. As noted in previous studies (Schrouff and Mourao-Miranda, 2018, Haufe et al, 2014, Weichwald et al, 2015, Kia et al, 2017), this however does not mean that the brain activity associated with anxiety (measured by the STAI-T score) is distributed over the wholebrain. For example, Schrouff and Mourao-Miranda (2018) have shown that when the predictive patterns are subtle (i.e.…”
Section: Resultsmentioning
confidence: 69%
“…Note that contributions of individual regions were very small, however, suggesting that predictions were based on the overall pattern rather than on a small combination of regions. As noted in previous studies (Schrouff and Mourao-Miranda, 2018, Haufe et al, 2014, Weichwald et al, 2015, Kia et al, 2017), this however does not mean that the brain activity associated with anxiety (measured by the STAI-T score) is distributed over the wholebrain. For example, Schrouff and Mourao-Miranda (2018) have shown that when the predictive patterns are subtle (i.e.…”
Section: Resultsmentioning
confidence: 69%
“…These shortcomings might be partly attributable to individual differences (see Section 4.2), but other influences must also be considered. Although we have visualized the trained models with the highest accuracy, accuracy and interpretability do not always correlate (94,95). The present study has demonstrated the improvement of decoding accuracy achieved by using complexity measure as an input, but when considering its interpretation, it might be better to apply some constraint to the interpretability, rather than merely improving the accuracy.…”
Section: Limitationsmentioning
confidence: 70%
“…This is an important conclusion as the univariate contrast is often referred to as the 'ground truth' and used for model optimization e.g. based on weight stability [3]. Regarding the machine learning models, FP are present for both machines, but only in cases of low SNR.…”
Section: Discussionmentioning
confidence: 97%
“…The latter shows the relative contribution of the individual features to the model and has been heavily used in the neuroimaging community to infer conclusions about brain structure/function. There has however been a recent debate on whether weight maps can provide information about the neural signals leading to a significant classification/regression model [1]- [3]. The authors of [1] indeed suggest that weight maps provide a poor recovery of the input neural signal and lead to false positives.…”
Section: Introductionmentioning
confidence: 99%